Non-codon Optimized PiggyBac Transposase Induces Developmental Brain Aberrations: A Call for in vivo Analysis - Vierl, Franziska; Kaur, Manpreet; Götz, Magdalena (Frontiers in Cell and Developmental Biology, 2021)
In this perspective article, we briefly review tools for stable gain-of-function expression to explore key fate determinants in embryonic brain development. As the piggyBac transposon system has the highest insert size, a seamless integration of the transposed sequence into the host genome, and can be delivered by transfection avoiding viral vectors causing an immune response, we explored its use in the murine developing forebrain. The original piggyBac transposase PBase or the mouse codon-optimized version mPB and the construct to insert, contained in the piggyBac transposon, were introduced by in utero electroporation at embryonic day 13 into radial glia, the neural stem cells, in the developing dorsal telencephalon, and analyzed 3 or 5 days later. When using PBase, we observed a non-cell autonomous increase in basal progenitor cells, often accompanied by folding aberrations. These effects were considerably ameliorated when using the piggyBac plasmid together with mPB. While size and strength of the electroporated region was not correlated to the aberrations, integration was essential and the correlation to the insert size implicates the frequency of transposition as a possible mechanism. We discuss this in light of the increase in transposing endogenous viral vectors during mammalian phylogeny and their role in neurogenesis and radial glial cells. Most importantly, we aim to alert the users of this system to the phenotypes caused by non-codon optimized PBase application in vivo.